South Asia Economic Focus, Fall 2018 : Budget Crunch - World Bank (World Bank, Washington, DC, 2018)
South Asia remains the fastest-growing region in the world and its performance has strengthened further. The external environment, while remaining conducive, has become more turbulent. Monetary policy is being adjusted accordingly, but fiscal policy is not equally responsive and fiscal deficits remain large. Despite strong demand from advanced economies and considerable depreciation of domestic currencies, imports are still growing stronger than exports in most countries. Rising oil prices add further pressure on South Asia’s high current account deficits. South Asia is expected to remain the fastest-growing region in the world and its performance could strengthen even further. Widening current account deficits and increased turbulence in international markets call for prudent economic policy, and fiscal discipline is at the core of prudent management. However, most South Asian countries generate low tax revenue. They also run large fiscal deficits, often amplified by economic shocks and political cycles, which limits their room to maneuver. Tax revenue increases with economic growth, but so does government expenditure. Since spending multipliers are positive, the procyclicality of spending amplifies boom-and-bust cycles instead of smoothening them. In several countries debt levels are high and hidden liabilities are a concern. Not all these patterns are present in all countries, but they combine into a specific set of challenges in each, putting fiscal matters at the core of development policy.